2016
DOI: 10.1007/s00126-016-0648-x
|View full text |Cite
|
Sign up to set email alerts
|

Noble gases fingerprint a metasedimentary fluid source in the Macraes orogenic gold deposit, New Zealand

Abstract: Ar ratios up to 200 times greater than air. Similarly, I/Cl ratios for fluids extracted from mineralised quartz are similar to those of brines from marine sediments that have interacted with organic matter and are ten times higher than typical magmatic/mantle fluids. The Macraes mineralising fluids were compositionally variable, reflecting either mixing of two different crustal fluids in the metasedimentary pile or a single fluid type that has had varying degrees of interaction with the host metasediments. Evi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 58 publications
(136 reference statements)
0
5
0
Order By: Relevance
“…The fluids trapped in both pyrite and quartz at Daping have consistent 40 Ar/ 36 Ar ratios ( Supplementary Data , Tables S1–2 ), resembling those in the Jiaodong gold deposits with a demonstrated strong mantle contribution [ 56 ], but differing from those of Macreas in New Zealand with a proposed predominantly crustal source (Fig. 4b, c ) [ 57 ]. All samples at Daping have 3 He/ 36 Ar ratios of 2–8 × 10 −3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The fluids trapped in both pyrite and quartz at Daping have consistent 40 Ar/ 36 Ar ratios ( Supplementary Data , Tables S1–2 ), resembling those in the Jiaodong gold deposits with a demonstrated strong mantle contribution [ 56 ], but differing from those of Macreas in New Zealand with a proposed predominantly crustal source (Fig. 4b, c ) [ 57 ]. All samples at Daping have 3 He/ 36 Ar ratios of 2–8 × 10 −3 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The noble gas and halogen contents and ratios of fluids trapped in ore minerals can constrain whether the fluid that exsolved from the basic magma has the capacity to generate gold ores, since the noble gases and halogens are normally stable during fluid transport [ 57 , 88 ] and therefore can effectively distinguish between different fluid reservoirs [ 89 ]. Previous He-Ar isotope analyses on fluid inclusions from gold-related pyrites yielded a range of 3 He/ 4 He of 0.1 to 1 R/Ra [ 54 , 90 ], suggesting a mantle contribution to the ore fluid [ 90 ].…”
Section: Discussionmentioning
confidence: 99%
“…The blue area is consistent with a mixing between mantle‐magmatic fluids that are enriched in 40 Ar and 3 He and a fluid with air or air saturated water (the blues star: 3 He/ 36 Ar = 1 × 10 −8 and 40 Ar/ 36 Ar = 296.6; Kendrick & Burnard, 2013). The blue area is built by plotting literature data of Figure 3 and it is representative of the mixing (Kendrick & Burnard, 2013 and references therein; Tang et al., 2017; Goodwin et al., 2017; Wu et al., 2018). (c) He‐Ar isotopes systematics of fluid inclusions (FIs) in quartz and dolomite.…”
Section: Resultsmentioning
confidence: 99%
“…Pyrite preserves Ar and He trapped in the FIs over time, so the 40 Ar*/ 4 He ratios coupled to the He isotopic ratios show clear mixing trends between crustal and mantle derived fluids (Hu et al, 2009). Previous studies of noble gases in quartz FIs showed preferential loss of He (Goodwin et al, 2017;Graupner et al, 2006;Stuart & Turner, 1992), thus, the resulting high values of 40 Ar*/ 4 He ratios in the trapped fluids are far from a trend of direct mixing between crustal and mantle components (Figure 9c). The 40 Ar*/ 4 He ratios in the FIs in the Zannone quartz veins are extremely high confirming a significant He loss (Figure 9c).…”
Section: Mixing Processes: Evidence From Noble Gasesmentioning
confidence: 92%
“…Gaboury (2013) provided the first independent validation of the pyrite-sourced sedimentary gold model. More recently, evidence for gold sourced from carbon-rich sedimentary rocks in orogenic gold deposits was provided by numerous other independent techniques, such as (1) noble gases in fluid inclusions at the Phanerozoic world-class Macraes mine (Goodwin et al 2017); (2) stable carbon isotope compositions of CO 2 -rich fluid inclusions hosted in mineralised quartz from Palaeoproterozoic gold deposits (Lüders et al 2015); (3) MIF-S (mass independent fractionation) isotope anomalies of Δ 33 S in pyrite from Archaean orogenic gold deposits (Agangi et al 2016; Selvaraja et al 2017; Godefroy-Rodríguez et al 2018; Kresse et al 2018); and (4) boron stable isotopes from tourmaline in Archaean (Molnár et al 2016) and Palaeoproterozoic orogenic gold deposits (Lambert-Smith et al 2016a).…”
Section: Sources Of Goldmentioning
confidence: 99%